ANALYSIS OF CHARACTER EDUCATION VALUES IN THE NOVEL LINTANG PERJALANAN GETIR A WOMAN BY NANA RINA: Analisis Nilai-Nilai Pendidikan Karakter dalam Novel Lintang Perjalanan Getir Seorang Perempuan Karya Nana Rina - Dody Irawan; Asri Lolita; Fabio Testy Arience Loren; Tessa Dwi Leoni; Musliha Wardana; Silvia Sinambela (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to describe the character education values contained in the novel Lintang: Perjalanan Getir Seorang Perempuan by Nana Rina. The method used in this research is descriptive qualitative. The main instrument in this study is the researcher herself, supported by data analysis guidelines. The data in this study consist of words or sentences found in the novel Lintang: Perjalanan Getir Seorang Perempuan by Nana Rina. The data collection techniques used include reading, quoting, analyzing data into a research work table, and finally drawing conclusions. The data analysis techniques used are data reduction, data presentation, and data validation, as well as data validity techniques. The results of this study show fifteen character education values found in the novel: (1) religious, (2) honest, (3) tolerance, (4) discipline, (5) hard work, (6) creativity, (7) independence, (8) curiosity, (9) national spirit, (10) appreciation of achievement, (11) friendliness/communicative, (12) love of peace, (13) fondness for reading, (14) social care, and (15) responsibility.